Differentiation of ROMK potency from hERG potency in the phenacetyl piperazine series through heterocycle incorporation. Issue 9 (1st May 2016) - Walsh, Shawn P.; Shahripour, Aurash; Tang, Haifeng; de Jesus, Reynalda K.; Teumelsan, Nardos; Zhu, Yuping; Frie, Jessica; Priest, Birgit T.; Swensen, Andrew M.; Alonso-Galicia, Magdalena; Felix, John P.; Brochu, Richard M.; et al.
Graphical abstract: Abstract: Following the discovery of small molecule acyl piperazine ROMK inhibitors and their initial preclinical validation as a novel diuretic agent, our group set out to discover new ROMK inhibitors with reduced risk for QT effects, suitable for further pharmacological experiments in additional species. Several strategies for decreasing hERG affinity while maintaining ROMK inhibition were investigated and are described herein. The most promising candidate, derived from the newly discovered 4- N -heteroaryl acetyl series, improved functional hERG/ROMK ratio by >10× over the previous lead. In vivo evaluation demonstrated comparable diuretic effects in rat with no detectable QT effects at the doses evaluated in an in vivo dog model.